Pengaruh Karakteristik Pemerintah Daerah Terhadap Tingkat Pengungkapan Sukarela Informasi Keuangan Pada Website Pemerintah Daerah (Studi Kasus Pemerintah Daerah Tingkat Provinsi Se – Indonesia) - Yulia Yustikasari (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2018)
This study aims to examine the characteristics of local governments affect the Level of Voluntary Disclosure of Financial Information on Local Government Websites. Testing the influence of independent variables to the dependent variable used multiple linear regression equation and using cross section data. The results of testing on hypotheses provide evidence that the independent variable of Local Government does not affect the Voluntary Disclosure Level of Financial Information on Local Government Website, In addition to variable Government Expenditure does not affect the Voluntary Disclosure of Financial Information at Local Government Website, for Debt Financing variables Local Government has significant effect on Voluntary Disclosure Level of Financial Information at Local Government Website, for variable of Local Governmental Size has no effect to Voluntary Disclosure Level of Financial Information on Local Government Website.